A study on ESKAPE pathogens the bad bug with no drug - Dr. K. Dinesh; Dr. Mowna Karthick (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: ESKAPE pathogens include Enterococcus faecium, Staphylococcus aureus, Klebsiella pnuemonia, Acienetobacter baumanii, Pseudomonas aeruginosa and Enterobacter species. Currently all these organisms are the main cause of hospital infections globally and they have the property to effectively escape the effect of antibacterial drugs. Unstoppable success of these superbugs will lead to unwinnable war. The success of these pathogens is mainly because of the mutations, modifications of LPS. As the crisis for the antibiotic resistance continues to grow, the latest IDSA (infectious disease society of America) “Bad Bugs, No Drugs” reports the urge for new antibiotics in the research and development pipeline and proposes steps to tackle the shortage. Objective: The aim of the study was to characterize the antimicrobial resistance in ESKAPE pathogens isolated from 330 culture positive clinical sample. Method: Antibiotic resistance was determined by VITEK 2 and manual method was done on Kirby baurer method. MIC was determined by VITEK 2 and E-Test according to CLSI guidelines. Result: Out of the total cases 63 percent of the culture has ESKAPE pathogens. Except for S. aureus multidrug resistance index of ESKAPE pathogens revealed on increasing trend. Conclusion: ESKAPE pathogens are commonly identified in alarming frequency and knowledge of antimicrobial resistance will be aided for empirical treatment.